Landslide Susceptibility Assessment in Kota Kinabalu, Sabah Using Analytical Hierarchy Process and Spatial Analysis Methods - Rodeano Roslee; Kamilia Sharir; Woon Zhan Wen; Arina Ismail; Dwa Desa Warnana; Juan Pandu Gya Nur Rochman; Amien Widodo (Geography, Earth Science and Environment: Research Highlights Vol. 1, 2024)
This chapter presents an in-depth analysis of landslide susceptibility in Kota Kinabalu, Sabah, utilizing the Analytical Hierarchy Process (AHP) integrated with advanced geospatial techniques. By synthesizing expert judgments and spatial data, a comprehensive Landslide Susceptibility Analysis (LSA) was developed, revealing critical insights into the geological and environmental factors contributing to landslide susceptibility. The findings indicate that geology, slope conditions, and hydrology are the most influential factors, significantly affecting the region’s landslide risk. The study’s results show that 2.78% of the area is categorized as Very Low Susceptibility, 14.14% as Low Susceptibility, 19.74% as Moderate Susceptibility, 51.63% as High Susceptibility, and 11.34% as Very High Susceptibility. This research demonstrates the applicability of the AHP method for susceptibility assessment, offering a reliable tool for disaster risk management and urban planning in regions with similar environmental settings. The integration of AHP with GIS provides a model for future research and practical applications in enhancing landslide risk assessment.